Pembuatan Plang Nama Usaha Sebagai Upaya Penguatan Identitas Visual pada UMKM Dodol Ibu Eli di Kecamatan Narmada, Kabupaten Lombok Barat - Ida Ayu Nursanty; I Gst Gede Narung; M Wahyullah; Surahman Hidayat; Rosyia Wardani (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This community service aims to strengthen the visual identity and enhance the attractiveness of the business through designing the business signboard for the Micro, Small, and Medium Enterprise (MSME) Dodol Ibu Eli in Narmada District, West Lombok Regency. Before the implementation, the MSME did not have a representative business signboard, making it difficult for customers from outside the area to locate the business. The program was carried out using a participatory approach through several stages, including field observation to identify the needs and location conditions, design discussions with the business owner, collaborative signboard production with a local printing partner, installation, and final evaluation. The results showed that the presence of the business name signboard successfully improved the professional image, strengthened local product branding, and made it easier for customers to recognize the business location. After installation, the business owner reported an increase in new customer visits and higher product sales compared to before the activity. This program is expected to serve as a reference for other MSME owners in recognizing the importance of visual identity as a key element of branding and sustainable business development strategies.